1997
DOI: 10.1159/000213845
|View full text |Cite
|
Sign up to set email alerts
|

Overactivity of Tumor Necrosis Factor-Alpha but Not Interleukin 6 Is Associated with Low Natural Killer Cytotoxic Activity in the Elderly

Abstract: In this paper we asked whether the increased production of two proinflammatory cytokines – tumor necrosis factor-α (TNFα) and interleukin-6 (IL6) in the absence of the inflammatory stimulus, a phenomenon frequently occurring in the elderly, may contribute to the decrease of natural killer (NK) cytotoxic activity. NK cell activity is a part of a nonspecific immunity directed against infected and transformed cells. We measured the levels of bioactive TNFα and IL6 during cytotoxic NK reactions and analyzed the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Nevertheless, we found that even in the population of apparently healthy old people (who did not, however, fulfil all SP criteria), NK activity was lower than that in young people [7]. These observations suggested that additional factors, and not only old age per se, could be responsible for the age-related preponderance of low NK activity in the healthy elderly.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…Nevertheless, we found that even in the population of apparently healthy old people (who did not, however, fulfil all SP criteria), NK activity was lower than that in young people [7]. These observations suggested that additional factors, and not only old age per se, could be responsible for the age-related preponderance of low NK activity in the healthy elderly.…”
mentioning
confidence: 55%
“…cytokines, may significantly contribute to this phenomenon. We have recently observed that low NK cytotoxic activity in the elderly was associated with a lack of full health and overactivity of tumor necrosis factor · (TNF·) but not interleukin-6 (IL-6) [7,20]. Interestingly, it has been shown that decreased serum T 3 levels correlate with increased plasma concentration of TNF· [21] and IL-2 [22] in old patients with nonthyroid illness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations